2021
DOI: 10.1002/lno.11719
|View full text |Cite
|
Sign up to set email alerts
|

Greening of the boreal peatland food web: Periphyton supports secondary production in northern peatlands

Abstract: Characterizing spatial and temporal variability of food web dynamics is necessary to predict how wetter and more nutrient-rich conditions expected with climate change will influence the fate of organic matter within northern peatlands. The goals of this study were to (1) document spatial and temporal variability in the contribution of periphyton to peatland food webs using isotope analysis ( 13 C and 15 N), and (2) quantify the influence of increased nutrient availability on primary and secondary production ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…A detailed description of the site's physical and chemical characteristics has been provided in Wyatt et al (2021). This fen has a top-down food web with three trophic levels (Ferguson et al 2021); algal biofilm, herbivores, and predatory macroinvertebrates (most of which are insect larvae). Common aquatic herbivore fauna (i.e., grazers) include wood frog tadpoles (Lithobates sylvaticus), snails (Lymnaea), tadpole shrimp (Notostraca), chironomid larvae (Diptera), and caddisfly larvae (Limnephilus).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description of the site's physical and chemical characteristics has been provided in Wyatt et al (2021). This fen has a top-down food web with three trophic levels (Ferguson et al 2021); algal biofilm, herbivores, and predatory macroinvertebrates (most of which are insect larvae). Common aquatic herbivore fauna (i.e., grazers) include wood frog tadpoles (Lithobates sylvaticus), snails (Lymnaea), tadpole shrimp (Notostraca), chironomid larvae (Diptera), and caddisfly larvae (Limnephilus).…”
Section: Methodsmentioning
confidence: 99%
“…During periods of inundation (i.e., the wet phase), the energy balance shifts to phototrophic microbes (i.e. algae) that form on peat surface layers (van Duinen et al 2013, Vesterinen et al 2016, Ferguson et al 2021. In contrast to recalcitrant plant material (e.g., mosses), this algae-based food web is susceptible to trophic regulation (DeColibus et al 2017.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The high gastropod density under sheltered conditions may be attributed to high food availability, especially the presence of macrophytes. Higher macrophyte biomass in the sheltered treatments can be grazed directly by gastropods but can also function as substrate to support periphyton growth, which is an important food resource for gastropods (Ferguson et al 2021). Although the periphyton biomass in the shelter treatment was significantly lower compared with the no shelter treatment, this may be explained by a high trophic transfer efficiency between periphyton and gastropods -supporting a high density of gastropods under sheltered conditions.…”
Section: Shelter Effect On Benthic Faunamentioning
confidence: 89%
“…I have shown that benthic algae (Chapter 3) or macrophytes (Chapter 4) were the dominant primary producers under sheltered conditions, which both could be grazed by gastropods (Schuler et al 2020, Chen et al 2020, Liu et al 2021. Moreover, higher macrophyte biomass under the sheltered conditions can not only serve as food and thereby directly benefit gastropods, but can also function as substrate to support periphyton growth, further provisioning food for gastropods (Ferguson et al 2021). Furthermore, the gastropods may also directly benefit from the calm conditions in the sheltered treatments as wind induced turbulence may increase their mortality and/or dislodgement Quinn 1988, Etter 1989).…”
Section: Increasing Food Web Complexitymentioning
confidence: 99%